Waveguide-Based All-Metal Near-Field Metasurfaces for Linearly and Circularly Polarized Beam Steering Antennas - Maira I. Nabeel; Muhammad U. Afzal; Khushboo Singh; Dushmantha N. Thalakotuna; Karu P. Esselle (IEEE Access)
This article presents an efficient near-field meta-steering antenna design using metasurfaces composed of waveguide-type, all-metal cells to achieve beam steering in both azimuth and elevation planes. The inherent rigidity of metallic metasurfaces at high temperatures ensures robust performance while maintaining the mechanical stability offered by the waveguide-based framework. The use of shielded cells in the metasurface design helps mitigate pattern variations caused by mutual coupling among cells. The Jerusalem cross slots used in the cells are polarization-insensitive and utilise a phase delay technique to tune the cell phase response. Experimental results demonstrate a steering range of ±34° in the elevation plane and a complete 360-degree coverage in the azimuth plane. The antenna exhibits a planar profile with metasurfaces placed in the near field directly over a waveguide adapter and has an overall height of 75 mm $(3λ _{o})$ at 12 GHz design frequency. Regardless of the rotation of the metasurfaces, the antenna is matched from 11.3 to 12.8 GHz, whereas the 3 dB gain bandwidth is 700 MHz (11.9-12.6 GHz).